Proceedings of the Ocean Drilling Program 1991
DOI: 10.2973/odp.proc.sr.118.156.1991
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic Evolution of the Atlantis II Fracture Zone

Abstract: SeaBeam echo sounding, seismic reflection, magnetics, and gravity profiles were run along closely spaced tracks (5 km) parallel to the Atlantis II Fracture Zone on the Southwest Indian Ridge, giving 80% bathymetric coverage of a 30-× 170-nmi strip centered over the fracture zone. The southern and northern rift valleys of the ridge were clearly defined and offset north-south by 199 km. The rift valleys are typical of those found elsewhere on the Southwest Indian Ridge, with relief of more than 2200 m and widths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
200
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(213 citation statements)
references
References 46 publications
(105 reference statements)
11
200
2
Order By: Relevance
“…The spacing of the gravity spikes along IC crust near the MAR axis ranges from 10 to 50 km, (Figure 8), similar to the spacing of fossil topographic highs on the transverse ridges bounding the Atlantis II Transform [Dick et al, 1991] and other MAR transverse ridges [Bonatti and Honnorez, 1976;Bonatti et al, 1983;Pockalny et al, 1988]. If, as proposed here, the gravity spikes are created by faults, the spacing implies that the formation of individual low-angle faults is a transient process that occurs episodically (every -2 m.y.).…”
Section: Role Of Transform Faultsmentioning
confidence: 78%
See 3 more Smart Citations
“…The spacing of the gravity spikes along IC crust near the MAR axis ranges from 10 to 50 km, (Figure 8), similar to the spacing of fossil topographic highs on the transverse ridges bounding the Atlantis II Transform [Dick et al, 1991] and other MAR transverse ridges [Bonatti and Honnorez, 1976;Bonatti et al, 1983;Pockalny et al, 1988]. If, as proposed here, the gravity spikes are created by faults, the spacing implies that the formation of individual low-angle faults is a transient process that occurs episodically (every -2 m.y.).…”
Section: Role Of Transform Faultsmentioning
confidence: 78%
“…We examine digital multibeam bathymetric and residual gravity data collected over four areas of the slow-spreading MAR Morris and Detrick, 1991; (Figure 1), two areas of the fast-spreading EPR between 7°-9"30'S [Wang and Cochran, 1993] and 8050 '-9°50*N [Madsen et al, 1990], and the very slow-spreading Southwest Indian Ridge (SWIR) near the Atlantis II Transform [Dick et al, 1991; Dick, unpublished data, 1990]. These data sets encompass a total of 8 transforms and 14 nontransform offsets with age offsets from 0.1 to 23 Ma and half-spreading rates from 0.8 to 7.7 cm/yr.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Geophysical surveys, ocean drilling holes, and submersible means provide indications for the present-day lower oceanic crust deformation. For instance, magnetic investigations [2, 5, 6] and structural studies [7,8] of the gabbroic section have shown that the lower crust is occasionally suffer significant rigid body rotation and is mostly decoupled from the upper crust. Yet, these views are either limited in their spatial coverage or provide indirect evidence for deformation.…”
Section: Introductionmentioning
confidence: 99%